Phase I/II trial of cabazitaxel plus abiraterone in patients with metastatic castration-resistant prostate cancer (mCRPC) progressing after docetaxel and abiraterone. (18th October 2016) - Massard, C.; Mateo, J.; Loriot, Y.; Pezaro, C.; Albiges, L.; Mehra, N.; Varga, A.; Bianchini, D.; Ryan, C. J.; Petrylak, D. P.; Attard, G.; Shen, L.; et al.
Abstract: Background: Abiraterone and cabazitaxel improve survival in patients with metastatic castration-resistant prostate cancer (mCRPC). We conducted an open-label phase I/II trial of cabazitaxel plus abiraterone to assess the antitumor activity and tolerability in patients with progressive mCRPC after docetaxel (phase I), and after docetaxel and abiraterone (phase II) (NCT01511536). Patients and methods: The primary objectives were to determine the maximum tolerated dose (MTD) and dose-limiting toxicities (DLTs) of cabazitaxel plus abiraterone (phase I), and the prostate-specific antigen (PSA) response defined as a ≥ 50% decrease confirmed ≥3 weeks later with this combination (phase II). Results: Ten patients were enrolled in the phase I component; nine were evaluable. No DLTs were identified. The MTD was established as the approved doses for both drugs (cabazitaxel 25 mg/m 2 every 3 weeks and abiraterone 1000 mg once daily). Daily abiraterone treatment did not impact on cabazitaxel clearance. Twenty-seven patients received cabazitaxel plus abiraterone plus prednisone (5 mg twice daily) in phase II. The median number of cycles administered (cabazitaxel) was seven (range: 1–28). Grade 3–4 treatment-emergent adverse events included asthenia (in 5 patients; 14%), neutropenia (in 5 patients; 14%) and diarrhea (in 3 patients; 8%). Nine patients (24%) required dose reductions of cabazitaxel. Of 26 evaluable patients, 12 achieved a PSA response [46%; 95% confidence interval (CI): 26.6–66.6%]. Median PSA-progression-free survival was 6.9 months (95% CI: 4.1–10.3 months). Of 14 patients with measurable disease at baseline, 3 (21%) achieved a partial response per response evaluation criteria in solid tumors. Conclusions: The combination of cabazitaxel and abiraterone has a manageable safety profile and shows antitumor activity in patients previously treated with docetaxel and abiraterone.